2006
DOI: 10.3892/or.16.5.1117
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of metronomic temozolomide treatment in patients with recurrent temozolomide-refractory glioblastoma

Abstract: Abstract. Frequent regular administration of chemotherapeutic agents at low doses, known as 'metronomic chemotherapy', can increase the anti-angiogenic activity of the drugs, as has been confirmed by several other experimental tumor models. The aim of this pilot study was to evaluate the efficacy and safety of metronomic temozolomide (TMZ) treatment in twelve consecutive patients with recurrent TMZrefractory glioblastoma. The patients were administered by metronomic treatment schedule (continuous low-dose chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Our results show that both monotherapies (TMZ alone and ZD6474 alone) efficaciously reduced tumor volume, corroborating with previous reports (7,8,13,(20)(21)(22), while a more marked tumor volume reduction (94%) was achieved with the combination treatment, due to the highly anti-angiogenic (64% reduction of MVD) and anti-proliferative (40% reduction) effects of the combined therapy. To further understand the mechanisms involved, future studies need to investigate the expression changes of angiogenic markers, such as VEGF and EGF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that both monotherapies (TMZ alone and ZD6474 alone) efficaciously reduced tumor volume, corroborating with previous reports (7,8,13,(20)(21)(22), while a more marked tumor volume reduction (94%) was achieved with the combination treatment, due to the highly anti-angiogenic (64% reduction of MVD) and anti-proliferative (40% reduction) effects of the combined therapy. To further understand the mechanisms involved, future studies need to investigate the expression changes of angiogenic markers, such as VEGF and EGF.…”
Section: Discussionsupporting
confidence: 92%
“…Its small size allows it to easily pass the blood-brain barrier and is therefore widely used in the clinic for the treatment of tumors of the central nervous system and metastatic melanoma (14,15). Previous literature has reported that low dose, metronomic TMZ administration leads to lower resistance to the drug and even inhibits angiogenesis (7,13). The present study also applied the low dose, metronomic TMZ therapy and observed a 80% reduction in tumor volume even with the single agent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 Retrospective studies and clinical trials with temozolomide in recurrent GbM (temozolomide + nitrosourea combination studies are described in Table 2 Table 3 Retrospective studies and clinical trials with temozolomide in recurrent GbM (temozolomide + nitrosourea combination studies are described in Table 2 (133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145). The toxicity profile did not vary between the different schemes.…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 99%
“…Many trials evaluating temozolomide in the recurrent setting have also included anaplastic glioma, which appears to be highly responsive to repeat temozolomide therapy 58 . 65,66,69 or to start with a 200 mg/ m 2 loading dose followed by a lower-dose regimen (for example, 90 mg/m 2 every 12 hours 68 ). With these various approaches, the estimated 6-month pfs rate has been reported to be 24%-44%.…”
Section: 61mentioning
confidence: 99%